ELECTRICAL CONDUCTIVITY IN METALS, SEMICONDUCTORS, AND DIELECTRICS (Ustozlar uchun, 2025)
This article provides an in-depth theoretical analysis of the electrical conductivity of solids. From a scientific perspective, it examines the electronic structure of metals, semiconductors, and dielectrics, the theory of energy bands, charge carrier mechanisms, as well as the effects of temperature, external electric fields, and impurities on electrical conductivity. The formulas presented serve as an important theoretical foundation for solid-state physics and modern electronics.